9-2y-6=11

Simple and best practice solution for 9-2y-6=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-2y-6=11 equation:


Simplifying
9 + -2y + -6 = 11

Reorder the terms:
9 + -6 + -2y = 11

Combine like terms: 9 + -6 = 3
3 + -2y = 11

Solving
3 + -2y = 11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2y = 11 + -3

Combine like terms: 3 + -3 = 0
0 + -2y = 11 + -3
-2y = 11 + -3

Combine like terms: 11 + -3 = 8
-2y = 8

Divide each side by '-2'.
y = -4

Simplifying
y = -4

See similar equations:

| y=1.9x+4.5 | | 2-3+7w=8w+3 | | 0.8(x+300)=0.84x-68 | | 7a+a+6b+2b+b= | | 10k-k-7k=10 | | 14+n+6=-5 | | 7=2.5lnx+3 | | -3(4x-1)-12=-105 | | -9+8v=7v | | 6x-8=-3x-116 | | y=-2x+3y | | 3.5v+8=12.5-video | | 8d-2d+12=42 | | 75y^3+25y^2-12y-4=0 | | 9-3-7y=-8-5y | | -8x-19=54-2x | | 5v+-15v+15v+9v-11v=-18 | | 8x-3x=4x+x | | 6r+12-4=20 | | B+2.4=9.2 | | 8x-8=8(x-6) | | 11c-16=15 | | 2c+3c=15 | | 3(21+15)=3(21)+3(15) | | B=9.2 | | 14-6a=7(-8a+2) | | 0.12(y-2)+0.04y=0.20y-0.05(10) | | t-6=8-t | | -12d+11d-14-10= | | -50+2x=25+7x | | -4*sin(2*x)=0 | | 9xx=225 |

Equations solver categories